Sandbox regulatório como instrumento fomentador da inovação no Brasil - Mendes, Hugo Cavalcanti Vaz (2023)
This research aims to analyze how regulatory sandboxes emerged and have been adopted in Brazil as a tool to foster innovation and economic-social development. First, it is provided the conceptualization of innovation and assessedhow it impacts and fosters economic development and the effective legal system. Then, it explores the regulatory race in which regulatory agents aim to review current regulations in order to cover technological innovations and their inherent risks. As a response to this regulatory challenge, regulatory sandboxesemerge, initially focused on solutions developed by fintechs in the financial market. This paper also seeks to highlight the main characteristics, benefits, objectives and challenges of this regulatory mechanism and to understand how such an international model, which emerged in the United Kingdom in 2016, has been implemented in Brazil, mainly by three agents: the Central Bank of Brazil, the Securities and Private Insurance Superintendence. Finally, other sandboxes possible applications out of the financial market are analyzed, namely for the study of artificial intelligence solutions, data protection and testing mechanisms for urban improvements